In Vitro Evaluation of Antifungal of Ungu Leaf (Graptophyllum Pictum L. Griff) Extract and Actinomycetes Isolates Against Candida albicans - Desya Rizqia Putri Khairani; Meiskha Bahar; Yuni Setyaningsih; Fajriati Zulfa (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
The high prevalence of infections caused by the opportunistic fungus Candida albicans encourages research to find alternative antifungals that are safer and more effective than synthetic drugs, which can cause side effects and resistance. This study aims to compare the antifungal potential of purple leaf extract (Graptophyllum pictum (L.) Griff) and Actinomycetes isolates against the growth of C. albicans using the Ultrasound-Assisted Extraction (UAE) method and tested by the well diffusion method at concentrations of 30; 40; and 50%. The results showed that purple leaf extract inhibited the growth of C. albicans with an average inhibition zone diameter between 16.475 mm to 18.2 mm, while Actinomycetes isolates showed a smaller inhibition zone, which was between 10.875 mm to 12.05 mm. Statistical analysis using the independent T-test and Mann-Whitney test confirmed a significant difference in inhibition between purple leaf extract and the Actinomycetes isolate at each concentration tested. The mechanism of action of both is by binding to ergosterol in the fungal cell membrane, forming complex compounds that result in increased permeability and ultimately inhibit fungal growth. Especially at 30% concentration, purple leaf extract showed the highest effectiveness with an average inhibition zone of 18.2 mm.